Enhancing Students’ Learning Outcomes in Islamic Education Through The Team Games Tournament (TGT) Method: A Study on The Fathu Makkah Lesson - Widiyanti, Endang (Jurnal Keprofesian Guru Keagamaan, 2025)
This study aims to enhance students’ learning outcomes in Islamic Education, particularly on the topic of Fathu Makkah, through the implementation of the Team Games Tournament (TGT) method. TGT, a cooperative learning model, emphasizes teamwork, competition, and active participation to improve students’ motivation and conceptual understanding. The research employed a Classroom Action Research (CAR) design conducted in two cycles, involving 30 fifth-grade students. Data were collected through learning achievement tests, observation sheets, and documentation. The findings reveal that the application of TGT significantly improved students’ learning outcomes and engagement. Students demonstrated greater enthusiasm, collaboration, and comprehension of the Fathu Makkah lesson through interactive learning activities. The method encouraged peer learning and provided a positive competitive atmosphere that enhanced both academic achievement and moral values such as cooperation and respect. These results highlight that the TGT method is an effective pedagogical approach for improving learning outcomes and fostering active participation in Islamic Education. Beyond academic gains, the model supports the development of character values aligned with Islamic teachings, making it a valuable strategy for teachers seeking to create dynamic, student-centered learning environments in primary Islamic education.